2021
DOI: 10.3390/nu14010066
|View full text |Cite
|
Sign up to set email alerts
|

Excess Folic Acid Supplementation before and during Pregnancy and Lactation Alters Behaviors and Brain Gene Expression in Female Mouse Offspring

Abstract: Use of folic acid (FA) during early pregnancy protects against birth defects. However, excess FA has shown gender-specific neurodevelopmental toxicity. Previously, we fed the mice with 2.5 times the recommended amount of FA one week prior to mating and during the pregnancy and lactation periods, and detected the activated expression of Fos and related genes in the brains of weaning male offspring, as well as behavioral abnormalities in the adults. Here, we studied whether female offspring were affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The experimental results showed that 1200 U/mL SOD can effectively relieve 2-cell block, but CoQ10 and FA did not. This may be due to the low toxicity of CoQ10 31 and FA 32 , and the fact that SOD, as an antioxidant enzyme, has a direct effect on oxidative damage. The following experiments were carried out to test whether adding 1200 U/mL SOD in a culture medium containing 10 –4 mol/L BPS can also improve other phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that 1200 U/mL SOD can effectively relieve 2-cell block, but CoQ10 and FA did not. This may be due to the low toxicity of CoQ10 31 and FA 32 , and the fact that SOD, as an antioxidant enzyme, has a direct effect on oxidative damage. The following experiments were carried out to test whether adding 1200 U/mL SOD in a culture medium containing 10 –4 mol/L BPS can also improve other phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal FA supplementation typically comprises three phases: pre-mating, gestation, and lactation. The pre-mating period varies in duration, from as short as one week [ 59 , 60 , 61 ] to as long as six weeks [ 62 ], as in the study by Henzel et al, where female mice received FA diets for six weeks before mating and then returned to a control diet [ 62 ]. In contrast, some studies applied FA diets during all three phases to mimic the FA supplementation scenario in the human population [ 60 , 61 , 63 ].…”
Section: Mouse Models To Study the Impact Of High-dose Maternal Folic...mentioning
confidence: 99%
“…In contrast, subsequent researchers reached a consensus that 2 mg FA/kg diet is the recommended level for rodents, and this criteria was applied to the most widely used with an AIN-93 diet [ 67 ]. As such, most recent studies used a control diet containing 2 mg/kg FA [ 56 , 57 , 58 , 60 , 61 , 63 ], with the exception of Henzel et al, who used a slightly different diet containing 2.3 mg/kg FA as the control [ 62 ]. For the FA-supplemented diet, Barua et al, who used 0.4 mg/kg FA for the control diet (CD), utilized 4 mg/kg FA, a tenfold higher level [ 59 ].…”
Section: Mouse Models To Study the Impact Of High-dose Maternal Folic...mentioning
confidence: 99%
See 2 more Smart Citations